Concept of circular economy in technical and vocational education: a systematic literature review - Ab Hamid, Norzaharah; Kamaruzaman, Fathiyah Mohd; Rasul, Mohamad Sattar (Institute of Advanced Engineering and Science, 2024)
Circular economy emphasizes the principles of reduce, reuse, and recycle. By adopting circular economy concepts in the food system, we can ensure a more resilient and sustainable food supply. Aligned with this, technical and vocational education (TVET) plays an important role in bridging environmental education and the circular economy. Within the realm of TVET, students receive comprehensive training and skill development encompassing subjects related to food preparation and production. Additionally, TVET extends its purview to cover essential areas, including sustainable resource management, renewable energy technology, waste management, and the implementation of environmentally friendly production processes. However, the lack of clear understanding of the circular economy in the education sector requires this to be explored more deeply. Therefore, this study was conducted to identify the nature of published scientific literature on this topic and what are the emerging themes of circular economy of food system in TVET education. A systematic literature review (SLR) was conducted using Scopus, Web of Science (WoS), Education Resources Information Center (ERIC) and Dimensions databases. The result from this analysis revealed that four themes emerged: i) skills and competency; ii) implementation in food system; iii) economy, social, and environmental (ESE) impact; and iv) delivery of content. Based on the derived theme, the concept of circular economy is discussed consisting of four pillars in order to provide a clear understanding about the relation of circular economy in TVET education. The findings of this study expand knowledge and the literature on the circular economy within the context of TVET.